The study of perception of residents on the impacts of landfill towards their property value / Nur Afifah Ahmad Subuki and Mohd Farid Sa'ad - Ahmad Subuki, Nur Afifah; Sa'ad, Mohd Farid (2019)
A landfill site which is also known as tip, dump or rubbish dump is the oldest form of waste treatment in the world. In this study, the objective is to examines whether true or not, house being located near to landfill has an impact on the residential property value. A conceptual framework was developed based on literature review of previous study. With the aim to accomplish of above, the quantitative method had been applied to collect the primary data by distributing 100 sets of questionnaire for resident live near to landfill in Papan, Lahat. The questionnaire has covered from the background of respondent, the current overview environment of the residential area, the opinion of respondent towards property value and the recommendation. By using Statistic Package for Social Science (SPSS) and Microsoft Excel, the data collected have been analyse. The result after calculating the mean distribution found that odour and air pollution are the current overview problems to the resident. While for the property, the result show that it gives bad impact to the infrastructure and facilities provided compared to the property value.